Pemberdayaan Kader Posyandu dalam Program Gerakan Amankan Kehamilan dan Persalinan (GEBRAK) dengan Mobile Application Family Center Maternity Care (FCMC) - Nicky Danur Jayanti; Senditya Indah Mayasari (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Efforts to accelerate the success of reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), especially those related to maternal health efforts, are increasing cross-sectoral partnerships as outlined in a high-risk pregnant women's mentoring activity by cadres carried out in Malang City known as the GEBRAK (Movement to Secure Pregnancy and Childbirth) program. "Posyandu Melati" cadre activities such as training or mentoring cannot be carried out regularly scheduled and have not been carried out by all posyandu posts because of several constraints. The purpose of this community service is to increase the participation of the Cadre of Pregnant Women with High Risk Pregnancies and provide training and community empowerment on early detection of High Risk Pregnancies using the FCMC Mobile Application media method in Tasikmadu Village totaling 7 people. Results: three activities, namely Training Activities and mentoring Posyandu Cadres with the topic of high-risk pregnancy, KSPR, and FCMC mobile application, the second activity is socialization and application of the FCMC Mobile Application to pregnant women and their families and communities. The last activity is the Recording and Early Detection of High Risk Pregnancies by Cadres as a support for the success of the GEBRAK program. Increasing the skills of Posyandu cadres about monitoring high-risk pregnancies so that prevention, healing and recovery efforts can be given with clear indications as early as possible during pregnancy. Posyandu cadres are expected to be able to carry out their duties according to agreed commitments and be able to maintain infrastructure as a good support for activities.